PENGEMBANGAN APOTEK HIDUP UNTUK KEMANDIRIAN KESEHATAN DI DESA REMBITAN: PEMANFAATAN TANAMAN OBAT KELUARGA - Maulana, Dimas Andrian; Putri, Rizka Ananda; Apriani, Ema Mita; Nasrullah, M. Andy Farhan; Maesa, Tithonia Prina; naufal, Muhammad Nabil; Uyun, Tasniatul; Maisarah, Khairinka Nurani; Nuzulilazmi, Qiraatin; Azhari, Yolanda Cahyani (Jurnal Wicara, 2024)
The development of a home-grown pharmacy (apotek hidup) in Rembitan Village was motivated by the community's need for health independence through the utilization of family medicinal plants. The program aims to reduce the community's dependence on chemical medications by providing accessible and affordable herbal treatment alternatives. The method used in this activity was a participatory approach, involving the community in the planting, care, and use of medicinal plants such as ginger, turmeric, lemongrass, and aloe vera. The results showed that the people of Rembitan Village were able to use these plants to treat various ailments such as coughs, inflammation, and digestive issues, while also preserving traditional herbal knowledge. The installation of educational posters in various strategic locations successfully increased community awareness and participation in the program. In conclusion, the home-grown pharmacy has significantly contributed to the health independence of the Rembitan Village community.